Pengembangan Media Pembelajaran MONRAKED (Monopoli Raksasa Edukatif) pada Materi Sistem Pencernaan - Nur Hafidzah; Jamilah Jamilah; Syamsul Syamsul; Ilyas Ismail (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to develop learning media MONRAKED (Educational Giant Monopoly) on the digestive system material for class XI SMA Pesantren GUPPI Samata Gowa Regency and determine the level of validit, practicality and effective of learning media MONRAKED (Educative Giant Monopoly) on digestive system material for class XI SMA Pesantren GUPPI Samata.This study uses research and development (R & D) methods referring to the 4-D development model which includes four stages, namely define, design, develop, and disseminate. The product developed is in the form of learning media MONRAKED (Educational Giant Monopoly) which is tested through validity tests, practicality tests and effectiveness tests. The subjects in this study were students of class XI MIA 1 SMA Pesantren GUPPI Samata 2020/2021 as many as 14 students. The research instrument is a student response questionnaire and a teacher response questionnaire to obtain product practicality data, as well as test items to obtain product effectiveness data.The results showed that the MONRAKED (Educational Giant Monopoly) learning media on the digestive system material for class XI SMA Pesantren GUPPI which was developed has a validity level by a team of material experts and a valid design expert team of 3.72, the assessment of student responses and teacher responses, the level of practicality is at practical category with an average total score of 2.64. The test of student learning outcomes using the learning media MONRAKED (Educational Giant Monopoly) on the digestive system material for class XI SMA Pesantren GUPPI Samata is categorized as effective because it reaches 100%. So the learning media MONRAKED (Educational Giant Monopoly) on the digestive system material for class XI SMA Pesantren GUPPI Samata is feasible to use because it has met the valid, practical and effective criteria.